2020
DOI: 10.1186/s12903-020-01323-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of crown to implant ratio and implantoplasty on the fracture resistance of narrow dental implants with marginal bone loss: an in vitro study

Abstract: Background Peri-implantitis is a biological complication that affects soft and hard tissues around dental implants. Implantoplasty (IP) polishes the exposed implant surface, to decontaminate it and make it less prone to bacterial colonization. This study investigates whether a higher clinical crown-to-implant-ratio (CIR) reduces implant fracture resistance and whether implants are more fracture-prone after IP in the presence of 50% of bone loss. Methods Forty-eight narrow platform (3.5 mm) 15 mm long titaniu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 33 publications
3
20
0
Order By: Relevance
“…It seems that MIs with MBR near the loading side may potentially be more prone to suffer from overloading than other implants. Leitão-Almeida et al 26 performed an in vitro study with narrow implants (3.5 mm) in a situation of 50% bone loss, which was similar to the resorption group in the present study. They concluded that increasing the clinical crown height significantly reduced the implant resistance to loading, and further led to the probability of fatigue fracture increased.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…It seems that MIs with MBR near the loading side may potentially be more prone to suffer from overloading than other implants. Leitão-Almeida et al 26 performed an in vitro study with narrow implants (3.5 mm) in a situation of 50% bone loss, which was similar to the resorption group in the present study. They concluded that increasing the clinical crown height significantly reduced the implant resistance to loading, and further led to the probability of fatigue fracture increased.…”
Section: Discussionsupporting
confidence: 82%
“… 20 24 The focus of this in vitro study was to investigate the biomechanical effect of MBR on the strain of the MI and the support of the MI-OD. In view of the acceptable bone loss 15 17 and pathological bone loss, combining with the previous studies conducted by Linetskiy et al 25 (assumed implants in 10+ years of service with 0.2 mm annual bone loss) and Leitão-Almeida et al 26 (simulated narrow implants in 50% height of bone loss), the resorption group in the present study was simulated in the situation of MI with bone loss to 1/2 length to provide information especially for extreme bone loss cases. The location and direction of the strain gauge was also a crucial factor.…”
Section: Discussionmentioning
confidence: 76%
“…1 ), and received a customized hemispherical loading abutment. The protocol used is similar to that described in a recent paper ( 14 ).…”
Section: Methodsmentioning
confidence: 99%
“…This procedure was similar to that described by Leitão-Almeida et al . ( 14 ), except for the amount of implant inserted in the resin and the length of the load abutment. In brief, 7.5 mm-high metal hemispheric load abutments (n=32) were placed on each implant using prosthetic screws (Avinent® Implant System, Santpedor, Spain) at 32 N/cm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation